EFL LECTURERS' AND STUDENTS' ACADEMIC WRITING EXPERIENCE AND CHALLENGES IN USING AI WRITING TOOLS: A QUALITATIVE STUDY - Meli Fauziah; Sarwo Edy; Abdul Karim Amrullah; Jesi Nuraini; Eka Apriani (Linguists : Journal of Linguistics and Language Teaching, 2025)
This study investigates the experiences and challenges of lecturers and students in the English Tadris Study Program of IAIN Curup in using AI writing tools for academic work. Using a qualitative approach with purposive sampling, data were collected from one lecturer and ten students through interviews, supported by a preliminary pilot study confirming the integration of AI in academic writing practices. The findings reveal that AI enhances idea development, organization, syntactic accuracy, vocabulary refinement, and writing confidence, functioning as a cognitive accelerator that streamlines the writing process. However, significant challenges emerge, including shallow idea generation, rigid structures, machine-like language, inaccurate citations, limited access to premium AI features, and insufficient prompt literacy. The discussion highlights deeper pedagogical implications, particularly the shifting paradigm from “writing as creation” to “writing as collaboration,” emphasizing the lecturer’s role as mediator of ethical AI use. Psychological transformations also appear, where efficiency leads to dependency, forming a “comfort paradox” that threatens independent thinking and authorial identity. The study concludes with recommendations for institutional AI guidelines, AI literacy integration, equitable access, and pedagogical redesign to balance automation with originality.